Synthesis and Characterization of Some New Hydrazides and Their Derivatives - S. Al-Ajely, Mohammad; N. Yaseen, Aymen (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
New hydrazide compounds (A2) and (A9) were prepared from their corresponding esters (A1, A8) .These esters were also prepared from their precursors 5-ethoxy carbonyl-(4methoxyphenyl)-6-methyl-1,2,3,4-tetrahydropyrimidine-2-thione (A1) via multicomponent reaction type and from hippuric acid respectively. The hydrazide compounds were then allowed to react with some aldehydes forming the corresponding hydrazones (A3-7) and (A1014). The synthesized compounds were characterized by IR, 1H-NMR, 13C-NMR, and Mass spectroscopies and well discussed. .